Effect of SLCO1B1 genotypes on statin intolerance and response to statins. (3rd October 2022) - Ghelani, R; Davis, L; Neves, E; Khaled, M; Khan, T Z
Abstract: Background: Statins are a cornerstone therapy for management of hypercholesterolaemia in primary and secondary prevention of cardiovascular disease, however there is individual variation regarding efficacy of therapy and adverse side-effects experienced. Purpose: Polymorphisms of the SLCO1B1 gene have shown correlation with the risk of statin side-effects and efficacy of treatment, however in real-world clinical practice, their utility remains to be established. Methods: We carried out retrospective multiple linear regression analysis using robust standard errors of 129 individuals undergoing genetic testing for the SLCO1B1 polymorphisms rs4149056 and rs2306283 to investigate for an association to statin side effects and efficacy respectively. In addition, logistic regressions which account for the binary nature of the outcomes were performed. The rs4149056 gene has 3 outcomes: T/T (considered least associated with statin intolerance), C/C (considered most associated with statin intolerance) and T/C (considered intermediately associated with statin intolerance). The rs2306283 gene has 3 outcomes: A/A (considered least associated with statin response), G/G (considered most associated with statin response) and A/G (considered intermediately associated with statin response). Results: According to multiple regression and logistic regression analyses SLCO1B1 rs4149056 genotypes (C/C and T/C relative to the base type T/T) do not predict the incidence of myalgia, myopathy, creatine kinase rise, liver function derangement or gastrointestinal side effects at 5% significance. SLCO1B1 rs2306283 (G/G and A/G relative to the base type A/A) do not predict LDL response to statins (p-values 0.33 and 0.52 respectively). Conclusions: The presence of rs4149056 C/C and T/C genotypes was not associated with an increased risk of statin side-effects. Similarly rs2306283 genotypes did not correlate with the efficacy of statin treatment. These genotype predictors were primarily based on Simvastatin – an earlier generation statin, whereas the majority of the patients in this cohort were treated with more contemporary and widely used statins such as Atorvastatin and Rosuvastatin. We therefore conclude that these genotypic markers may have limited application in modern day clinical practice and that substantial investment of limited resources towards them may not be justified. Funding Acknowledgement: Type of funding sources: None.